2021
DOI: 10.1111/anae.15595
|View full text |Cite
|
Sign up to set email alerts
|

Early cryoprecipitate transfusion versus standard care in severe postpartum haemorrhage: a pilot cluster‐randomised trial

Abstract: There is a lack of evidence evaluating cryoprecipitate transfusion in severe postpartum haemorrhage. We performed a pilot cluster-randomised controlled trial to evaluate the feasibility of a trial on early cryoprecipitate delivery in severe postpartum haemorrhage. Pregnant women (>24 weeks gestation), actively bleeding within 24 h of delivery and who required at least one unit of red blood cells were eligible. Women declining transfusion in advance or with inherited clotting deficiencies were not eligible. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The rate of refusal to consent was low (9.5%). Anonymised routine data in the absence of consent was collected in 25.1% of cases, because participants were not given study documentation prior to hospital discharge or could not be contacted postdischarge 17…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of refusal to consent was low (9.5%). Anonymised routine data in the absence of consent was collected in 25.1% of cases, because participants were not given study documentation prior to hospital discharge or could not be contacted postdischarge 17…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol (including patient-facing documentation) and findings in relation to the feasibility of intervention delivery and main study outcomes are published separately. 17 18 Advance consent for participation was waived with Research Ethics Committee approval (Ref: 18/LO/2062). Women in both intervention and control sites were approached by the research team postnatally for written, informed consent to collect their routine, deidentified, clinical data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replenishing these components is important for forming stable clots and hemostasis. Recent studies have demonstrated the benefits of early replenishment of fibrinogen, namely faster bleeding control resulting in improved outcomes, among pediatric [ 5 ], trauma [ 6 ], and post-partum hemorrhage [ 7 ] patients, making a strong argument to address these deficiencies earlier. The positive impact such care has on patient blood management and overall blood utilization [ 8 ], at a time when blood supplies are strained, furthers the need for early administration of fibrinogen and key clotting factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several challenges present when institutions attempt to implement earlier cryo AHF administration, largely associated with the product’s limited post-thaw shelf life of 4–6 h, resulting in an inability to prepare the product in advance of requirement without meaningful logistical challenges and wastage [ 6 , 15 , 16 ] that govern the timing of product availability. Two recent studies—Curry et al and Green et al—focused on the feasibility of transfusing cryo AHF into actively bleeding patients within 90 min and experienced several obstacles in achieving the target [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%